2022
DOI: 10.1038/s41598-022-07414-x
|View full text |Cite|
|
Sign up to set email alerts
|

Long COVID in hospitalized and non-hospitalized patients in a large cohort in Northwest Spain, a prospective cohort study

Abstract: Survivors to COVID-19 have described long-term symptoms after acute disease. These signs constitute a heterogeneous group named long COVID or persistent COVID. The aim of this study is to describe persisting symptoms 6 months after COVID-19 diagnosis in a prospective cohort in the Northwest Spain. This is a prospective cohort study performed in the COHVID-GS. This cohort includes patients in clinical follow-up in a health area of 569,534 inhabitants after SARS-CoV-2/COVID-19 diagnosis. Clinical and epidemiolog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
2
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 24 publications
4
65
2
6
Order By: Relevance
“…Parosmia and other smell disorders were most commonly reported in the non-hospitalized group of patients which is in accordance with previous reports showing that olfactory dysfunction appears to be a component of LongCOVID, with parosmia as a prominent symptom in almost half of those with smell loss [ 28 ]. In a recent study byPérez–González et al, extra-thoracic symptoms (39.1%), chest symptoms (27%), dyspnoea (20.6%) and fatigue (16.1%) were more common in hospitalized patients (52.3% vs. 38.2%) and in women (59.0% vs. 40.5%) [ 29 ]. In another recent study byAli et al, non-hospitalized COVID-19 patients continue to experience neurologic symptoms, fatigue, and compromised quality of life 14.8 months after initial infection [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parosmia and other smell disorders were most commonly reported in the non-hospitalized group of patients which is in accordance with previous reports showing that olfactory dysfunction appears to be a component of LongCOVID, with parosmia as a prominent symptom in almost half of those with smell loss [ 28 ]. In a recent study byPérez–González et al, extra-thoracic symptoms (39.1%), chest symptoms (27%), dyspnoea (20.6%) and fatigue (16.1%) were more common in hospitalized patients (52.3% vs. 38.2%) and in women (59.0% vs. 40.5%) [ 29 ]. In another recent study byAli et al, non-hospitalized COVID-19 patients continue to experience neurologic symptoms, fatigue, and compromised quality of life 14.8 months after initial infection [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…56 Research at https://doi.org/10.1017/cts.2022.425 Published online by Cambridge University Press the end of 2021 and in 2022 suggests that people who are not hospitalized also have significant PASC symptoms. [57][58][59][60] The first 15 published studies on PASC identified 55 different symptoms, while patient-led initiatives have identified over 205 PASC-related features. 53 Studies use different terms for similar symptoms and cover very different timelines ranging from two weeks after onset of symptoms to more than 6 months.…”
Section: Lack Of Clear Definitions Of Pascmentioning
confidence: 99%
“…A review of prospective studies on the natural history of PASC suggests that the majority of studies recruit hospitalized patients; it remains unclear if ICU patients, hospitalized patients, and nonhospitalized patients have different PASC symptoms and needs [56]. Research at the end of 2021 and in 2022 suggests that people who are not hospitalized also have significant PASC symptoms [57][58][59][60].…”
Section: Lack Of Clear Definitions Of Pascmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, has become a global health problem worldwide [ 1 ]. Moreover, along with its development, SARS-CoV-2 mutated into various variants, such as Alpha, Beta, Gamma, Delta, Omicron, Lambda, and Mu, drawing the world’s attention.…”
Section: Introductionmentioning
confidence: 99%